Rogi Parīkṣā And Roga Parīkṣā: An Ayurvedic Perspective On Clinical Examination And Diagnosis (The Review of Diabetic Studies, 2025)
Rogi Parīkṣā and Roga Parīkṣā constitute the fundamental principles of Ayurvedic clinical examination and diagnosis. Ayurveda emphasizes that accurate diagnosis requires not only scientific knowledge and technical skill but also empathy, observation, communication, and understanding of the patient. Classical Ayurvedic texts describe various methods of examination such as Dvividhā, Trividhā, Caturvidhā, Ṣaḍvidhā, Aṣṭavidha, Daśavidha, and Dvādaśavidha Parīkṣā for comprehensive assessment of the patient and disease. The concepts of Nidāna Pañcaka and Pramāṇas such as Āptopadeśa, Pratyakṣa, Anumāna, and Yukti provide a systematic framework for diagnosis and understanding of Samprāpti (pathogenesis). The present article reviews the principles, methods, and clinical importance of Rogi Parīkṣā and Roga Parīkṣā as described in classical Ayurvedic literature.